PENETAPAN POSISI DI BENAK KONSUMEN (POSITIONING) MUSEUM NEGERI NTB BERDASAR PERSEPSI PENGUNJUNG - khairany, Kurnia; Saufi, Akhmad; Rinuastuti, Baiq Handayani (Master of Management, Mataram University, 2017)
This study aimed to determining the positioning of the State Museum of West Nusa Tenggara based on visitor’s perception. The research method used was qualitative approach with data collecting through interview, observation and documentation. Informants is selected by accidental sampling technique. Data from interviews with 20 informants were analyzed using content analysis method. The results showed that the State Museum of West Nusa Tenggara hada positioning as edutainment with dimensions of value, uniqueness, credibility, sustainability and conformity. The museum should consider the desire and needs of visitors with the main purpose of the museum, which is to present the mission of education as well as entertainment to the public. Thus, the Museum of West Nusa Tenggara is expected to be a place to gain knowledge and experience as well as recreation that reaches all levels of society. The most important contribution of this study is the positioning model of the State Museum of West Nusa Tenggara based on the perception of visitors i.e. edutainment concept to become a pioneer for further empirical research. It is expected that in the future the managerial of West Nusa Tenggara State Museum can increase visit to the museum. Keywords: Museum, positioning, visitor perceptions, edutainment